(untitled) (Journal of Pharmaceutical Negative Results, 2010)
The present study was undertaken to investigate antidepressant activity of ethanolicextract of Beta vulgaris [BV], by using forced swim test [FST] and tail suspension test[TST] in mice. Imipramine [10 mg/kg, i.p.] used as the standard drug significantlydecreased immobility time in both TST and FST, while BV [50 and 100 mg/kg, i.p.]significantly increased immobility time in TST and FST. This suggests that BV hasdepressant activity and not antidepressant activity